Challenges for Medical Student in the Society 5.0 Era - Sri A Ibrahim (Jambura Medical and Health Science Journal, 2023)
Background: For health workers, the faster flow of globalization develops many challenges. Indonesia's health workers also face internal challenges. In contrast, in the 5.0 society era, the challenges are in the form of an emphasis on the quality of character, morality, and competence of the health workers.Content: A medical student should be formed in the Community and Family Health Care with Inter-Professional Education (CFHC-IPE) education program, which develops competencies related to ethics, communication, teamwork, and roles and responsibilities in a team from the first day at college. The new challenge for medical education is applying the three new literacies, namely data, technology, and humanity, to produce Indonesian doctors who can adapt and meet national and global needs. Every graduate must meet the competency standards of doctors, which not only provide services to the community through professional practice but can also maintain the noble values of the medical profession.Conclusion: Medical students in the 5.0 era have challenges that take work, particularly in developing new skills in data literacy, technology, and humanity, while still fulfilling their primary competencies.